2018
DOI: 10.1007/s10854-018-8770-4
|View full text |Cite
|
Sign up to set email alerts
|

Influence of thiourea on the synthesis and characterization of chemically deposited nano structured zinc sulphide thin films

Abstract: Nanocrystalline ZnS thin films incorporated onto glass substrates by chemical bath deposition method were investigated by X-Ray Diffraction (XRD), Atomic Force Microscopy (AFM), UV-Visible Spectroscopy (UV-Vis), Photoluminescence (PL), and Raman Spectroscopy (FT-R) studies. The influence of thiourea on the structural and optical properties of ZnS films was discussed in detail. The X-ray diffraction patterns confirmed the rhombohedral structure of ZnS thin films. AFM measurements indicated the nano carpet-like … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 47 publications
(59 reference statements)
0
7
0
Order By: Relevance
“…The presence of thiourea detected through XPS suggest a second partial interpration of the increased optical band gap of the CuSCN-NP compared to bulk CuSCN as extrapolated from the Tauc plot in Fig. 1d: a previous literature report on a similar case 32 describes how the band gap of a ZnS thin films resulted to be singificantly affected by the presence of residual thiourea precursor, when a chemical bath deposition process was employed to fabricate it. Attempts to perform local structural analysis through selected area electron diffraction (SAED) during TEM imaging were unsuccessful (at both high, 200 kV, and low, 80 kV, acceleration voltages), due to instability of the particles under the electron beam during data acquisition 33 , a behavior that is compatible with the presence of beam-sensitive hydrated CuS x phases.…”
Section: Resultsmentioning
confidence: 65%
“…The presence of thiourea detected through XPS suggest a second partial interpration of the increased optical band gap of the CuSCN-NP compared to bulk CuSCN as extrapolated from the Tauc plot in Fig. 1d: a previous literature report on a similar case 32 describes how the band gap of a ZnS thin films resulted to be singificantly affected by the presence of residual thiourea precursor, when a chemical bath deposition process was employed to fabricate it. Attempts to perform local structural analysis through selected area electron diffraction (SAED) during TEM imaging were unsuccessful (at both high, 200 kV, and low, 80 kV, acceleration voltages), due to instability of the particles under the electron beam during data acquisition 33 , a behavior that is compatible with the presence of beam-sensitive hydrated CuS x phases.…”
Section: Resultsmentioning
confidence: 65%
“…For ZnS thin films deposited at bath temperatures more than 70°C, the particle size and growth rate obviously increase as shown in Figures 4 and 5 for bath temperatures 75°C and 80°C, respectively, for different deposition times (20,30,40, and 50 min). At t d = 30 min, the average grain size was 187 nm and 228 nm for bath temperatures 75°C and 80°C, respectively.…”
Section: Resultsmentioning
confidence: 87%
“…The AFM micrograph of ZnS films deposited at bath temperature T b = 65°C for different times of deposition (t d = 20, 30, 40, 50 min) is shown in Figure 1. From AFM images, it is observed that unclear structures formed at lower deposition times (20,30, and 40 min) so it could not be able to measure their diameters. At t d = 50 min, small spherical ZnS-NPs appeared with the mean grain diameter of 120 nm approximately.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations